Adaptation of Popular Names of Ornamental Plants in Indonesia - Harum Munazharoh; Arum Rindu Sekar Kasih; Gulita Evapraja (Universitas Airlangga, 2023)
This article explores the phenomenon of popular names for ornamental plants in Indonesia, emphasizing their role as both identifiers and representations of economic value. The popularity of these names is categorized based on their alignment (or lack thereof) with different parts of the ornamental plants. Employing a descriptive linguistic approach, the reference attributes of popular names are systematically grouped, followed by an image search and identification of their biological counterparts. The study also traces the elements contributing to the formation of names and their lexical meanings, incorporating both internal and external equivalents. Interviews with traders and collectors further support the meaning search, employing directional techniques and documenting substantive ethnographic patterns. A total of 85 names were collected from ornamental plant traders and collectors, supplemented by data from specialized YouTube channels. These popular names are further classified into nine categories based on plant attributes, such as structure (stalks, leaves, stems, and flowers), time, character, place, sound, and direction. The diversity in plant naming correlates with a complexity that extends beyond language, namely social class, selling price, and aesthetic considerations. Additionally, the naming process revolves around human preferences for convenience, practicality, and cultural phenomena. Changes in the naming of ornamental plants in Indonesia have substantial implications for shifting trends in people's preferences, as evidenced by the dimming landscape of post-pandemic YouTube channels and the ornamental plant market.